Homologous regions within M protein genes in group A streptococci of different serotypes. - Scott, J R (1986)
DNA hybridization with probes from the structural gene for the M6 protein shows that the carboxy-terminal region (proximal to the cell surface) is conserved among strains of different M serotypes. The amino-terminal region, which is more available to immunological surveillance, exhibits greater variation.